2016
DOI: 10.1259/bjr.20160509
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and clearance of retained gadolinium in the brain: differences between linear and macrocyclic gadolinium based contrast agents in a mouse model

Abstract: Cite this article as: Kartamihardja AAP, Nakajima T, Kameo S, Koyama H, Tsushima Y. Distribution and clearance of retained gadolinium in the brain: differences between linear and macrocyclic gadolinium based contrast agents in a mouse model. Objective: To investigate the distribution and clearance of retained gadolinium (Gd) in various parts of the brain after intravenously administering a Gd-based contrast agent (GBCA) in normal and renal failure mouse models. Methods: Two different mouse models: normal (n 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
40
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 33 publications
(45 reference statements)
6
40
1
Order By: Relevance
“…7,9,11 In several human 27,28 and animal studies, 23,33,34 the concentration of Gd in these brain structures has been shown to be significantly above background values. These observations raised the question about the underlying mechanism of Gd retention in the brain and the chemical species of the present Gd.…”
Section: Discussionmentioning
confidence: 99%
“…7,9,11 In several human 27,28 and animal studies, 23,33,34 the concentration of Gd in these brain structures has been shown to be significantly above background values. These observations raised the question about the underlying mechanism of Gd retention in the brain and the chemical species of the present Gd.…”
Section: Discussionmentioning
confidence: 99%
“…In a subsequent study with the same protocol, the same team demonstrated that, in the various brain areas of both renally impaired and naive mice treated with gadodiamide, the Gd clearance was limited over the time. 49 …”
Section: Discussionmentioning
confidence: 99%
“…With a median cumulative dose of 6.83 mmol/animal (range 0.54 to 16.65mmol/ animal) the clinical dataset shows much less cumulative GBCA dose as compared to published reports from human medicine [1] or animal experiments. [53] Even if a superior brain clearance of macrocyclic GBCAs over linear GBCAs is described [54,55] and all dogs of this study got a linear GBCA administration, the cumulative dose did not reach a visible level of hyperintensities after 2-3 administrations. We determined mean SI ratio differences between first and last MRI examination between 0.2% and 6.9% (range -12.5% to 13.8%), which was not significantly different from 0.…”
Section: Discussionmentioning
confidence: 74%